Services marketing : integrating customer focus across the firm - Zeithaml, Valarie A.; Bitner, Mary Jo; Gremler, Dwayne D. (Dubuque : McGraw-Hill Education, 2018)
"This text is for students and business people who recognize the vital role that services play in the economy and its future. The advanced economies of the world are now dominated by services, and virtually all companies view service as critical to retaining their customers today and in the future. Manufacturing and product-dominant companies that, in the past, have depended on their physical products for their livelihood now recognize that service provides one of their few sustainable competitive advantages"--
"Zeithaml's Services Marketing introduces readers to the vital role that services play in the economy and its future. Services dominate the advanced economies of the world, and virtually all companies view services as critical to retaining their customers. The seventh edition maintains a managerial focus by incorporating company examples and strategies for addressing issues in every chapter, emphasizing the knowledge needed to implement service strategies for competitive advantage across industries. New research references and examples in every chapter include increased coverage of new business model examples such as Airbnb, Uber, OpenTable, Mint/Intuit, and others, alongside greater emphasis on technology, digital and social marketing, Big Data, and data analytics as a service. View Table of Contents and Features below for more information"--
Revised edition of the authors' Services marketing, c2013
Includes bibliographical references and index
1
Keywords: BUSINESS & ECONOMICS -- Marketing -- Multilevel; Customer services; Marketing; Service industries -- Marketing